Virtual Network Embedding Algorithm for Diverse Service Request - Hua Qu; Lixia Wang; Jihong Zhao; Henan Wang (Dianxin kexue)
Network virtualization is the main means of solving the ossification problem, and resource allocation is the core of network virtualization. Unbalanced resource distribution and low virtual network acceptance ratio have been caused by diversifying services whose requests of virtual nodes and virtual links have great disparity. In order to solve these problems, virtual network embedding algorithm for diverse service requests was proposed. First, it defined node saturation which reflects resource ration between node and its connected links. Then, it mapped virtual nodes to substrate nodes whose minimum node saturation was closest to the one of virtual nodes. At last, it mapped virtual links to substrate paths which were composed of substrate links based on the constraints of mapped substrate nodes and node saturation. Simulation result shows that the proposed algorithm can satisfy diverse service requests and get higher virtual network acceptance ratio and resource utilization ratio.